2019
DOI: 10.1016/j.neuint.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Roles for the uptake2 transporter OCT3 in regulation of dopaminergic neurotransmission and behavior

Abstract: Transporter-mediated uptake determines the peak concentration, duration, and physical spread of released monoamines. Most studies of monoamine clearance focus on the presynaptic uptake transporters SERT, NET and DAT. However, recent studies have demonstrated the expression of the uptake transporter OCT3 (organic cation transporter 3), throughout the rodent brain. In contrast to NET, DAT and SERT, OCT3 has higher capacity and lower affinity for substrates, is sodium-independent, and is multi-specific, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Although Mayer et al (2018) reported that midbrain dopamine neurons express OCT3 mRNA in mice, an immunohistological study by Cui et al (2009) found that OCT3 was expressed by astrocytes and non-dopamine neurons in the SNC but not by dopamine neurons. Although it is uncertain if dopamine neurons express OCT3, OCT3 has been shown to be insensitive to cocaine (Gasser, 2019;Mayer et al, 2018), which would agree with our finding that dopamine (in the presence of an AMPK inhibitor) can evoke an inward current despite the presence of a DAT inhibitor. If dopamine can be transported by OCT3 into dopamine neurons, our results would suggest that this transporter is tonically inhibited by AMPK.…”
Section: Alternate Sites For Dopamine Uptakesupporting
confidence: 88%
“…Although Mayer et al (2018) reported that midbrain dopamine neurons express OCT3 mRNA in mice, an immunohistological study by Cui et al (2009) found that OCT3 was expressed by astrocytes and non-dopamine neurons in the SNC but not by dopamine neurons. Although it is uncertain if dopamine neurons express OCT3, OCT3 has been shown to be insensitive to cocaine (Gasser, 2019;Mayer et al, 2018), which would agree with our finding that dopamine (in the presence of an AMPK inhibitor) can evoke an inward current despite the presence of a DAT inhibitor. If dopamine can be transported by OCT3 into dopamine neurons, our results would suggest that this transporter is tonically inhibited by AMPK.…”
Section: Alternate Sites For Dopamine Uptakesupporting
confidence: 88%
“…Studies examining the relative subcellular localizations of DAT and OCT3 and their proximity to dopamine receptors would be particularly informative. While colocalization of these transporters has not been examined (Gasser, 2018), ultrastructural studies have demonstrated that OCT3 is localized to dendritic spines and presynaptic terminals in the BLA (Gasser et al., 2017), suggesting important roles for the transporter in regulating perisynaptic monoamine concentrations. OCT3 expression has also been observed on DAT+ neurons (Mayer et al., 2018), suggesting possible co‐expression at dopamine terminals.…”
Section: Discussionmentioning
confidence: 99%
“…These transporters also function to clear monoamines from the extracellular fluid and are inhibited to CORT. Among the Uptake 2 transporters, OCT3 has the highest sensitivity to CORT (Gasser, 2018) and is expressed at greater density in the NAcc and BLA than other OCT isoforms (Amphoux et al., 2006). PMAT is expressed in relatively similar levels between the NAcc and BLA (Dahlin, Xia, Kong, Hevner, & Wang, 2007) and has greater affinity for dopamine than norepinephrine (Duan & Wang, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCTs are polyspecific, electrogenic, pH-and Na + -independent, but voltage-dependent bidirectional transporters for OCs with species-and tissue-specific expression. 1 Indeed, OCTs are considered to be an important regulator of monoamine neurotransmitter concentration in the CNS, [2][3][4][5] and, because of their high expression in secretory organs such as the liver (OCT1) and the kidneys (OCT2), they play an important role in OC excretion. This fact is of particular importance considering their interaction with drugs such as the antidiabetic metformin and the anticholinergic drug trospium, whose excretion is mediated by OCT1 and OCT2.…”
Section: Introductionmentioning
confidence: 99%